2021
DOI: 10.3390/ijerph18158184
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 on Surfaces in Households of Persons with COVID-19

Abstract: SARS-CoV-2 transmission from contaminated surfaces, or fomites, has been a concern during the COVID-19 pandemic. Households have been important sites of transmission throughout the COVID-19 pandemic, but there is limited information on SARS-CoV-2 contamination of surfaces in these settings. We describe environmental detection of SARS-CoV-2 in households of persons with COVID-19 to better characterize the potential risks of fomite transmission. Ten households with ≥1 person with laboratory-confirmed COVID-19 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 27 publications
3
46
0
Order By: Relevance
“…Despite existing COVID-19 control measures, surface sampling identified potential deficiencies in routine disinfection procedures that informed targeted strengthening of infection control practices to support workplace re-opening. Similar to other SARS-CoV-2 outbreak studies, relatively low-level contamination was identified even in locations associated with recent occupancy of symptomatic people [5][6][7][8][9][10]. No positive surface sample yielded complete genome sequence suggesting degradation of the viral genome and a lack of transmission potential at the time of sampling.…”
Section: Discussionsupporting
confidence: 72%
“…Despite existing COVID-19 control measures, surface sampling identified potential deficiencies in routine disinfection procedures that informed targeted strengthening of infection control practices to support workplace re-opening. Similar to other SARS-CoV-2 outbreak studies, relatively low-level contamination was identified even in locations associated with recent occupancy of symptomatic people [5][6][7][8][9][10]. No positive surface sample yielded complete genome sequence suggesting degradation of the viral genome and a lack of transmission potential at the time of sampling.…”
Section: Discussionsupporting
confidence: 72%
“…Of 63 studies testing for SARS-CoV-2 RNA on surfaces, only 13 attempted to isolate infectious virus. Of these, viable SARS-CoV-2 virus was identified in only four instances: frozen cod packaging ( Liu et al, 2020 ), a nightstand of an infected case ( Marcenac et al, 2021 ), an isolation room of patients undergoing mechanical ventilation ( Ahn et al, 2020 ), and on a windowsill of a patient's quarantine unit ( Santarpia et al, 2020 ). In a cold-chain food setting, evidence is lacking on the frequency of SARS-CoV-2 contamination on packaging and the infection risks to workers.…”
Section: Introductionmentioning
confidence: 99%
“…The transmission of SARS-CoV-2 from contaminated surfaces or fomites has been a concern during the COVID-19 pandemic. Households have been important sites of SARS-CoV-2 transmission due to prolonged contact with an infected person and environmental contamination in these settings [38].…”
Section: Sars-cov-2 In Households With Covid-19 Casesmentioning
confidence: 99%
“…SARS-CoV-2 RNA detection rates varied from 0% to 37.5%. Most of the Ct values were ≥30 (30)(31)(32)(33)(34)(35)(36)(37)(38)(39), which assumes a low viral load. The investigation confirmed that 9/15 (60.0%) of the tested locations were contaminated with SARS-CoV-2, with one or more positive samples per location.…”
Section: Sars-cov-2 In Households With Covid-19 Casesmentioning
confidence: 99%